Experimental constraints on transient glacier slip with ice-bed separation - Nathan T. Stevens; Dougal D. Hansen; Lucas K. Zoet; Peter E. Sobol; Neal E. Lord (Journal of Glaciology)
Fast glacier motion is facilitated by slip at the ice-bed interface. For slip over rigid beds, areas of ice-bed separation (cavities) can exert significant control on slip dynamics. Analytic models of these systems assume that cavities instantaneously adjust to changes in slip and effective pressure forcings, but recent studies indicate transient forcings violate this—and other—underlying assumptions. To assess these incongruities, we conducted novel experiments emulating hard-bedded slip with ice-bed separation under periodic effective pressure transients. We slid an ice-ring over a sinusoidal bed while varying the applied overburden stress to emulate subglacial effective pressure cycles observed in nature and continuously recorded mechanical and geometric system responses. We observed characteristic lags and nonlinearities in system responses that were sensitive to forcing periodicity and trajectory. This gave rise to hysteresis not predicted in analytic theory, which we ascribed to a combination of geometric, thermal and rheologic processes. This framework corroborates other studies of transient glacier slip and we used it to place new constraints on transient phenomena observed in the field. Despite these divergences, average system responses converged toward model predictions, suggesting that analytic theory remains applicable for modeling longer-term behaviors of transiently forced slip with ice-bed separation.